The Phoenicians - Elayi, Josette (Lockwood Press, 2018)
Intro -- Title page -- Copyright page -- Table of contents -- Preface -- Introduction -- Part One: Phoenicia before 1200 -- 1. The Prehistory of Phoenicia (ca. 700,000-3200) -- 2. Byblos and Egypt (3200-1500 BCE) -- 3. The Other Proto-Phoenician Cities (3200-1500) -- 4. The Small Vassal States of the Near East (1500-1200) -- Part Two. The Period of Phoenicia's Independence (1200-883) -- 1. The Emergence of Phoenicia (around 1200) -- 2. Egypt's Loss of Influence in Phoenicia (1200-1000) -- 3. Early Assyrian Exploration towards the West (1100-1000) -- 4. Dynastic Crises in Byblos (1000-900) -- 5. The Development and Expansion of the Phoenician Cities (1000-883) -- Part Three. Phoenicia under Assyrian Domination (883-610) -- 1. The Beginnings of Assyrian Expansion (883-745) -- 2. The Conquest of the West by the Assyrians (745-721) -- 3. Domination of Phoenicia by the Sargonids (721-610) -- Part Four. Phoenicia under Babylonian Domination (610-539) -- 1. Phoenicia between Egypt and Babylonia (610-605) -- 2. The Peak of the Babylonian Empire (605-562) -- 3. The Decline of the Babylonian Empire (562-539) -- Part Five. Phoenicia under Persian Domination (539-332) -- 1. The Establishment of the Persian Empire (539-479) -- 2. The Development of the Persian Empire (479-404) -- 3. The Persian Empire in Turmoil (404-333) -- 4. The Fall of the Persian Empire (333-330) -- Conclusion -- Maps -- Tables -- Bibliography -- Index of Persons, Deities, Peoples,and Ancient Authors.